The Impact of Certain Price of Natural Gas Policy on Indonesia’s Economy - Indah Prasetyawati; Djoni Hartono (Muhammadiyah University Press, 2023)
The Indonesian national industry has experienced a slowdown in growth and decrease in competitiveness, allegedly caused by the high price of natural gas. Therefore, the government intervened by implementing Certain Price of Natural Gas Policy (Harga Gas Bumi Tertentu), a policy that facilitates industries to obtain gas at lower prices through the issuance of Presidential Decree Number 121 of 2020 concerning Natural Gas Pricing. This study aims to analyze the impact of the policy on the national economy by considering the decline in state revenues as a consequence of the reduced price of natural gas for industry. Using the Computable General Equilibrium (CGE) model, analyses were carried out on various economic indicators. This study finds a decline in GDP for 0.076% in the short-run and an increase in GDP for 0.004% in the long-run. Furthermore, household income, in both rural and urban areas, decreases from 0.1 to 0.2% in both short and long-run. For industries that use gas intensively, the price reduction increases sectoral output and labor, and reduces commodity prices.